Evaluating factors affecting implementation of community-based tsetse control in southern Burkina Faso. Part 1: Use of insecticide impregnated screens - Kamuanga, M.; Kabore, I.; Swallow, B.M.; Amsler-Delafosse, S.; Bauer, B. (OAU/STRC, 1995)
Tsetse control programme using traps, targets and trypanocide pour-on in Sissili, agro-pastoral zone of Burkina Faso, started in 1994 after an epidemics of animal trypanosomiasis which has destroyed almost 70 percent of cattle population. This area has been occupied by Fulani pastorlists of a government project seeking to increase livestock production. In order to prepare the community to praticipe more to tsetse control programme a study of family heads has been carried out to assess their disposition to contribute to tsetse control as well as to the social economic factors which affect the amount of resources in which they were ready to contribute. The results of a prompt evaluation study shows that 94 percent of households would be envolved in monetary and labor contribution. The willingness of bringing finiancial contribution has promoted better understanding that the concerned has on the symptoms of animal trypanosomiasis. The willigness to contribute through work was positively related to the number of years where they were set in time and space devoted to the community tasks. These results and the collected information on the existing local organizations functionining are utilized to create now organizations by virtue of local participation sustained to tsetse control.